2017
DOI: 10.1186/s13046-017-0635-9
|View full text |Cite|
|
Sign up to set email alerts
|

Direct inhibition of ACTN4 by ellagic acid limits breast cancer metastasis via regulation of β-catenin stabilization in cancer stem cells

Abstract: BackgroundPharmacology-based target identification has become a novel strategy leading to the discovery of novel pathological biomarkers. Ellagic acid (EA), a dietary polyphenol compound, exhibits potent anticancer activities; however, the underlying mechanisms remain unclear. The current study sought to determine the role and regulation of ACTN4 expression in human breast cancer metastasis and EA-based therapy.MethodsThe anti-metastasis ability of EA was validated by MMTV-PyMT mice and in vitro cell models. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 49 publications
3
40
1
Order By: Relevance
“…For example, ACTN4 promotes the proliferation of melanoma through regulating the stability of RIPK1 28 . ACTN4 inhibition suppresses cell proliferation and metastasis in breast cancer 29 . The current study proved that ACTN4 was highly expressed in PCa tissues and cells.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…For example, ACTN4 promotes the proliferation of melanoma through regulating the stability of RIPK1 28 . ACTN4 inhibition suppresses cell proliferation and metastasis in breast cancer 29 . The current study proved that ACTN4 was highly expressed in PCa tissues and cells.…”
Section: Discussionsupporting
confidence: 59%
“…28 ACTN4 inhibition suppresses cell proliferation and metastasis in breast cancer. 29 The current study proved that ACTN4 was highly expressed in PCa tissues and cells. And HOXA11-AS could upregulate ACTN4 expression by competitively binding with miR-518b in PCa.…”
Section: Discussionsupporting
confidence: 57%
“…ACTN4, known as an actinin-binding protein, is important for the regulation of cytoskeletal integrity and cell movement. Previous studies showed that it has a critical role in the pathogenesis of cancer due to its ability to promote cancer cell invasion and metastasis, as well as signaling pathways regulation [13,[24][25][26]. An et al indicated that ACTN4 induces EMT through the AKT signaling pathway in cervical cancer [12].…”
Section: Discussionmentioning
confidence: 99%
“…We investigated whether ellagic acid can be a useful agent for metastatic alteration of gastric cancer cells caused by the acidosis. Ellagitanins and their derivatives from black raspberry or pomegranate have shown inhibitory effects on several types of malignancies, including breast, ovarian, and prostate cancer, in studies in vivo and in vitro [16,[21][22][23]. The majority of previous studies have focused on the cytotoxic and cytostatic activity of ellagic acid in various types of cancers.…”
Section: Discussionmentioning
confidence: 99%